Analysis of International Law Regarding Human Trafficking: Efforts and Obstacles in Enforcement - Grenaldo Ginting; Asfahani Asfahani; Ghana Digfijay (Edujavare Publishing, 2024)
This research provides a comprehensive analysis of international legal frameworks addressing human trafficking, focusing on the efforts and obstacles in their enforcement. By examining key instruments such as the United Nations Palermo Protocol and various regional agreements, the study evaluates their effectiveness in preventing trafficking, protecting victims, and prosecuting perpetrators. The research results reveal significant disparities in adopting and implementing these frameworks across different countries, highlighting challenges such as limited resources, political will, and corruption. Additionally, the research underscores the complexity of trafficking networks and the need for enhanced international cooperation and intelligence sharing. It also addresses the critical issues of victim protection and the dual role of technology in both facilitating and combating trafficking. The study concludes with recommendations for improving legal frameworks, enhancing victim support, and leveraging technological advancements to more effectively combat human trafficking globally.